Algae as an alternative source of protein in poultry diets for sustainable production and disease resistance: present status and future considerations - Abdel-Wareth, Ahmed A. A.; Williams, Ayanna Nate; Salahuddin, Md; Gadekar, Sachin; Lohakare, Jayant (Frontiers in Veterinary Science, 2024)
Integrating algae into poultry diets offers a promising avenue for enhancing nutrition, boosting sustainability efforts, and potentially stimulating disease resistance. This comprehensive review delves into the essence, diversity, chemical composition, and nutritional merits of algae, spotlighting their emergence as innovative nutrient sources and health supplements for poultry. The growing interest in algae within poultry nutrition stems from their diverse nutritional profile, boasting a rich array of proteins, lipids, amino acids, vitamins, minerals, and antioxidants, thus positioning them as valuable feed constituents. A key highlight of incorporating both macroalgae and microalgae lies in their elevated protein content, with microalgae varieties like Spirulina and Chlorella exhibiting protein levels of up to 50–70%, outperforming traditional sources like soybean meal. This premium protein source not only furnishes vital amino acids crucial for muscular development and overall health in poultry but also serves as an exceptional reservoir of omega-3 fatty acids, notably eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), presenting multiple health benefits for both poultry and consumers alike. Moreover, algae boast antioxidant properties attributed to bioactive compounds like phycocyanin and astaxanthin, mitigating oxidative stress and boosting the bird’s immune response, thereby fostering robust health and disease resilience. Incorporating macroalgae and microalgae into poultry diets yields positive impacts on performance metrics. Research evidence underscores the enhancement of growth rates, feed conversion ratios, carcass quality, and meat attributes in broilers, while in layers, supplementation promotes increased egg production, superior egg quality, and increased concentrations of beneficial nutrients such as omega-3 fatty acids. Furthermore, algae hold promise for mitigating the environmental footprint of poultry production, though significant outcomes from trials remain sporadic, necessitating further research to elucidate optimal dosages and blends for different algae species in poultry diets. Standardizing the composition of algae utilized in research is imperative, paving the way for potential applications in poultry nutrition as growth stimulants and substitutes for antibiotics. Nonetheless, a deeper understanding of dosage, combination, and mechanism of action through rigorous scientific investigation is key to unlocking algae’s full potential within poultry nutrition.